PENGGUNAAN METODE DEMONSTRASI DALAM PEMBELAJARAN PRAKTIK WUDHU DENGAN KITAB DURŪS AL-FIQHIYYAH DI PPTQ AL-ASY'ARIYYAH 10 - Ahmad Taufiqurrohman; Desi Oktavia; Sekar Najwa Sal Sabila; Nurul Hikmah; Fatkhurrohman Fatkhurrohman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Learning the practice of wuḍūʾ is an essential component of fiqh education, as it directly affects the validity of prayer. However, in pesantren learning practices, some students are still found to perform wuḍūʾ incorrectly and not in accordance with fiqh regulations. This study aims to describe the use of the demonstration method in teaching the practice of wuḍūʾ using the book Durūs al-Fiqhiyyah at PPTQ Al-Asy’ariyyah 10 Al-Asy’ariyyah, to identify supporting and inhibiting factors in its implementation, and to analyze the impact of the use of the demonstration method on students’ understanding and skills. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that the use of the demonstration method was implemented through the stages of preparation, implementation, and evaluation, with Durūs al-Fiqhiyyah serving as the theoretical foundation. Supporting factors included the competence of teachers, a pesantren environment that supports the habituation of worship, and the availability of learning facilities, while inhibiting factors involved limited instructional time, a large number of students, and differences in students’ levels of understanding. The impact of using the demonstration method was reflected in improved students’ comprehension of the pillars and sequence of wuḍūʾ as well as enhanced skills in performing wuḍūʾ correctly and orderly. Therefore, the use of the demonstration method has a positive contribution to wuḍūʾ practice learning and is appropriate to be further developed in fiqh learning within pesantren contexts.